(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2025)
Pop culture festivals of a cultural and entertainment nature affect the recognition and popularity of a given area in the field of event tourism, which is currently one of the most important categories of the tourist product. The main aim of the research was to assess the pop culture festival in the category of a tourist product. The analytical part of the work used the netnographic method. As part of the netnographic study, the main fanpage of the Pyrkon Fantasy Festival was analyzed due to the intensity of words appearing in the posts. Then, the components of the tourist product, which is the pop culture festival, were identified. As a result of the conducted analyses, the research hypothesis was confirmed, according to which the pop culture festival is a complex tourist product with an extensive intangible sphere.